2016
DOI: 10.1016/j.cropro.2015.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Development of a qPCR for Leifsonia xyli subsp. xyli and quantification of the effects of heat treatment of sugarcane cuttings on Lxx

Abstract: The main control practice of Leifsonia xyli subsp. xyli (Lxx) in sugarcane is to heat-treat cane 15 cuttings used as planting material in an attempt to eradicate the bacterium. A real time 16 quantitative PCR (qPCR) protocol specific for Lxx was developed to assess the effectiveness of 17 this practice. Primers were designed from the sequence of an Lxx-specific gene and detected as 18 were collected from plant canes with low bacterial titers whereas in the second they were 22 collected from first-ratoon canes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 16 publications
(5 reference statements)
1
20
0
2
Order By: Relevance
“…None of the treatments completely eliminated Lxx from the setts. These outcomes corroborate those of Carvalho et al (2016), who developed a protocol to assess different heat treatment combinations, using quantitative PCR, and also found that the heat treatment only reduced bacterial levels in treated setts. Quantitative PCR also demonstrated that the decrease was greater in setts treated for more than one hour at temperatures of 50 ºC and 52 ºC, if compared to shorter treatments and the control.…”
Section: Bp →supporting
confidence: 85%
“…None of the treatments completely eliminated Lxx from the setts. These outcomes corroborate those of Carvalho et al (2016), who developed a protocol to assess different heat treatment combinations, using quantitative PCR, and also found that the heat treatment only reduced bacterial levels in treated setts. Quantitative PCR also demonstrated that the decrease was greater in setts treated for more than one hour at temperatures of 50 ºC and 52 ºC, if compared to shorter treatments and the control.…”
Section: Bp →supporting
confidence: 85%
“…Genomic DNA of the collected samples were extracted according to the instructions of TIANamp Bacteria DNA Kit (Bionicle Genomic DNA Extraction Kit (Tiangen, Beijing, China); DP302). The amplification of a 106‐bp fragment of Lxx DNA was obtained using primer sets of Lxx12950F1/R1 (F1: 5'‐GCACATCGATCTGGAAAAAAGG‐3', and R1, 5'‐GGATTCGGTTCTCATCTCAGC‐3') (Carvalho et al ). Genomic DNA of Lxx was used to prepare the standard curve according to the Ct values obtained after serial dilutions of Lxx DNA.…”
Section: Methodsmentioning
confidence: 99%
“…Control measures for ratoon stunt in China include its timely diagnosis in plants, as well as meristem tissue cultures, the sterilization of harvesting and planting equipment, and seedcane heating treatment (Sheng, Chen, Yang, & Deng, ). The last of these treatments, seedcane thermotherapy and equipment disinfection, have only limited efficacy, however, and cannot be used to completely eradicate Lxx (Carvalho et al., ). At the same time, meristem tissue culture consumes both time and resources (Zhang et al., ).…”
Section: Introductionmentioning
confidence: 99%